2013
DOI: 10.1007/s10120-013-0320-4
|View full text |Cite
|
Sign up to set email alerts
|

Stratified phase II trial to establish the usefulness of the collagen gel droplet embedded culture-drug sensitivity test (CD-DST) for advanced gastric cancer

Abstract: BackgroundWe conducted a multicenter phase II trial to assess the suitability of three types of chemotherapy (docetaxel plus S-1, irinotecan plus S-1, or S-1 alone) for patients with advanced gastric cancer by means of the collagen gel droplet embedded culture-drug sensitivity test (CD-DST). To our knowledge, this is the first multicenter clinical trial that has employed CD-DST to choose anticancer agents for the treatment of advanced gastric cancer.MethodsSubjects (n = 64) were patients with advanced or recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 19 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…Collagen gel droplet-embedded culture drug sensitivity test (CD-DST) uses an image colorimetric method to assess the combination of an anticancer drug and microcollagen gel embedded in a three-dimensional serum-free culture medium (3 to 10x10 3 cells/30 µg/drop) (5,6). It is a susceptibility test that is currently widely applied in various clinical fields, including gastrointestinal cancer (7)(8)(9). However, reports on the use of CD-DST in OSCC were few and none have evaluated multidrug combination chemotherapy or IACRT.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen gel droplet-embedded culture drug sensitivity test (CD-DST) uses an image colorimetric method to assess the combination of an anticancer drug and microcollagen gel embedded in a three-dimensional serum-free culture medium (3 to 10x10 3 cells/30 µg/drop) (5,6). It is a susceptibility test that is currently widely applied in various clinical fields, including gastrointestinal cancer (7)(8)(9). However, reports on the use of CD-DST in OSCC were few and none have evaluated multidrug combination chemotherapy or IACRT.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, 100 µl of culture medium was added in each well of E-Plate 96 (Acea Biosciences) to obtain equilibrium. 2x10 4 cells for cell line cells or 1x10 5 for human primary HCC cells in 100 µl of culture medium were seeded in E-Plate 96, which was coated by biocompatible microelectrode. After 18 h, cells were treated with 25, 12.5, 6.26, 3.13 and 1.56 µM, respectively.…”
Section: Cell Viability Assay Cell Viability Was Monitored By Xcel-mentioning
confidence: 99%
“…One part of the primary HCC cells was used for cell viability test monitored by xCEL-Ligence RTCA. The rest part of the cells was performed using collagen gel droplet-embedded CD-DST followed by the standard procedure (5). Briefly, HCC cells were cultured in the collagen droplet which provided a 3-D environment for HCC cells.…”
Section: Cell Viability Assay Cell Viability Was Monitored By Xcel-mentioning
confidence: 99%
“…No systematic research has demonstrated the exact thymic tumor responses to chemotherapy. Former studies have indicated that the collagen gel droplet embedded culture‐drug sensitivity test (CD‐DST) could approximate the clinical effect in different types of malignant tumors and have a high predictive accuracy for response to chemotherapy, reaching up to 84.1% . In this study, we report on the chemosensitivity of 100 patients with TETs by CD‐DST.…”
Section: Introductionmentioning
confidence: 96%